The latent structure of Acute Stress Disorder symptoms in trauma‐exposed children and adolescents. (30th July 2016) - McKinnon, Anna; Meiser‐Stedman, Richard; Watson, Peter; Dixon, Clare; Kassam‐Adams, Nancy; Ehlers, Anke; Winston, Flaura; Smith, Patrick; Yule, William; Dalgleish, Tim
Abstract : Background: The revision of Acute Stress Disorder (ASD) in the DSM‐5 ( DSM‐5, 2013) proposes a cluster‐free model of ASD symptoms in both adults and youth. Published evaluations of competing models of ASD clustering in youth have rarely been examined. Methods: We used Confirmatory Factor Analysis (combined with multigroup invariance tests) to explore the latent structure of ASD symptoms in a trauma‐exposed sample of children and young people ( N  = 594). The DSM‐5 structure was compared with the previous DSM‐IV conceptualization (4‐factor), and two alternative models proposed in the literature (3‐factor; 5‐factor). Model fit was examined using goodness‐of‐fit indices. We also established DSM‐5 ASD prevalence rates relative to DSM‐IV ASD, and the ability of these models to classify children impaired by their symptoms. Results: Based on both the Bayesian Information Criterion, the interfactor correlations and invariance testing, the 3‐factor model best accounted for the profile of ASD symptoms. DSM‐5 ASD led to slightly higher prevalence rates than DSM‐IV ASD and performed similarly to DSM‐IV with respect to categorising children impaired by their symptoms. Modifying the DSM‐5 ASD algorithm to a 3+ or 4+ symptom requirement was the strongest predictor of impairment. Conclusions: These findings suggest that a uni‐factorial general‐distress model is not the optimal model of capturing the latent structure of ASD symptom profiles in youth and that modifying the current DSM‐5 9+ symptom algorithm could potentially lead to a more developmentally sensitive conceptualization.